Family policy in comparative perspective: the concepts and measurement of familization and defamilization - Henning Lohmann; Hannah Zagel (Journal of European Social Policy, 2016)
Family policy is not easily conceptualized or measured in comparative research. Previous approaches are highly diverse and have yielded mixed empirical results in terms of placing countries' family policy profiles in the international landscape and mapping their trajectories. This article reviews the long-standing discussion of the familization and defamilization concepts popular in comparative research, derives a conceptual framework and provides an in-depth discussion of current empirical approaches. It tackles the lacking consensus on how familization and defamilization are measured, arguing that interventions in gender-specific and intergenerational dependencies are the key dimensions and that measurement at policy level is best suited to capture within- and cross-country variation in family policy. Using data on 21 European countries, the article proposes measures that acknowledge the different dimensions of familization and defamilization. The proposed indicators prove to be useful for mapping a range of European countries' family policy constellations but are bound by data restrictions. Therefore, the article makes a strong claim for improving the availability of internationally comparable family policy data.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; defamilization; familization; individualization; measurement